Directions of knowledge and schools in historiography - R. Torstendahl (Ученые записки Казанского университета: Серия Гуманитарные науки)
After a short terminological introduction, this article discusses the origin of schools as collective knowledge producers. European historiography had not seen such schools until Leopold von Ranke started his teaching, which included historical research through seminars. His school became paradigmatic. However, from the late 19th century, nationalist historians, who rallied around political ideas rather than around new historical knowledge, challenged the Rankean conception. Another challenge came from historians gathering around a French journal, the Annales. From Marc Bloch and Lucien Febvre, these historians had different ideas about historical research, but there were links between the conceptions of history in the second and third generation of editors. Thereby, they also came to precede the present with its different directions of historiography based on ideas of fruitful areas for research.